Biodegradable copolymers with succinimide and lactic acid units. Part II. Kinetics of thermodegradation, thermal characteristics and zeta potential of the product - Tudorachi, N.; Chiriac, A. P. (Polimery, 2011)
Biodegradable copolymers based on succinimide and lactic acid units prepared by two synthesis routes (variants A and B described in Part I, see [11]) were characterized. Variant A consists in the in situ copolymer synthesis using maleic anhydride, ammonium hydroxide and L(+)-lactic acid and accordingly variant B previously prepared poly(succinimide) is modificated be means of L(+)-lactic acid by mass polycondensation procedure. A comparison of thermodegradation kinetics (TG, DTG), thermal properties (DSC, DTG) and zeta potential was compared for the products obtained through both procedures. Differences in the thermal properties of the copolymers - especially in the glass transition temperatures - were observed.